Dydaktyka literatury i jej powiązania z innymi naukami w świetle wybranych prac dydaktyków zachodnioniemieckich = Literary didactics and its connections with other sciences in the light of chosen papers of west german scientists - Kozłowski, Aleksander; Marchewa, Janusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Basing on accessible papers, the authors present, in critical analysis, the opinions of some West German scientists on literary didactics as the science. The authors point out three trends of its development in West Germany: 1) theories connected with the science about literature, 2) theories connected with pedagogics, 3) autonomus theories with interdisciplinary character.Problems, given in this article, parcicularly with methodological character are coincident to the tendendes of researches carried out in Poland mainly by W. Pasterniak and U. Krauze
Keywords: dydaktyka literatury; nauka; pedagogika; Niemcy